Sublimable Single Ion Magnets Based on Lanthanoid Quinolinate Complexes: The Role of Intermolecular Interactions on Their Thermal Stability - Canon-Mancisidor, W; Canon-Mancisidor, W (American Chemical Society, 2018)
We report the design, preparation, and characterization of two families of thermally robust coordination complexes based on lanthanoid quinolinate compounds: [Ln(5,7-Br2q)4]- and [Ln(5,7-ClIq)4]-, where q = 8-hydroquinolinate anion and Ln = DyIII, TbIII, ErIII, and HoIII. The sodium salt of [Dy(5,7-Br2q)4]- decomposes upon sublimation, whereas the sodium salt of [Dy(5,7-ClIq)4]-, which displays subtly different crystalline interactions, is sublimable under gentle conditions. The resulting film presents low roughness with high coverage, and the molecular integrity of the coordination complex is verified through AFM, MALDI-TOF, FT-IR, and microanalysis. Crucially, the single-molecule magnet behavior exhibited by [Dy(5,7-ClIq)4]- in bulk remains detectable by ac magnetometry in the sublimated film. © 2018 American Chemical Society.